Near-atomic resolution reconstructions using a mid-range electron microscope operated at 200 kV - Campbell, Melody G. (J Struct Biol, 2014)
A new era has begun for single particle cryo-electron microscopy (cryoEM) which can now compete with X-ray crystallography for determination of protein structures. The development of direct detectors constitutes a revolution that has led to a wave of near-atomic resolution cryoEM reconstructions. However, regardless of the sample studied, virtually all high-resolution reconstructions reported to date have been achieved using high-end microscopes. We demonstrate that the new generation of direct detectors coupled to a widely used mid-range electron microscope also enables obtaining cryoEM maps of sufficient quality for de novo modeling of protein structures of different sizes and symmetries. We provide an outline of the strategy used to achieve a 3.7 Å resolution reconstruction of Nudaurelia capensis ω virus and a 4.2 Å resolution reconstruction of the Thermoplasma acidophilum T20S proteasome.